Collider prospects for the muon g - 2 in a general two-Higgs-doublet model - Hou, Wei-Shu; Jain, Rishabh; Kao, Chung; Kumar, Girish; Modak, Tanmoy (Physical review, 2021)
Recent progress on muon g−2 measurement prompts one to take it even more seriously. In the general two Higgs doublet model that allows extra Yukawa couplings, we take a simplified approach of single enhanced coupling. We fix the charged lepton flavor violating coupling, ρτμ=ρμτ, via the one-loop mechanism, for illustrative masses of the heavy scalar H and pseudoscalar A, where we assume mA=mH+. Since extra top Yukawa couplings are plausibly the largest, we turn on ρtt and find that LHC search for gg→H,A→τμ gives a more stringent bound than from τ→μγ with the two-loop mechanism. Turning on a second extra top Yukawa coupling, ρtc, can loosen the bound on ρtt, but LHC constraints can again be more stringent than from B→Dμν versus Deν universality. This means that evidence for H,A→τμ may yet emerge with full LHC Run 2 data, while direct search for τ±μ∓bW+ or t¯cbW+ (plus conjugate) may also bear fruit.
Gesehen am 31.03.2022